Птицы скалистых берегов р. Днестр – 40 лет спустя - Цвелых, А.Н.; Клестов, Н.Л.; Осипова, М.А. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
Avifauna of rocky banks of the Dniester River within bilateral border of Ukraine and Moldova is investigated.